The Construction Of Ethical Competence In The Perception Of Primary Care Nurses - Rafaela Schaefer; José Roque Junges (SciELO, 2014)
The study intended to understand the perception of nurses of Primary Care Services about the construction of ethical competence on their formation and practices. This is a qualitative study, with an interpretative phenomenological approach and interviews with ten nurses of the community health services of Porto Alegre, RS. The results showed that the interviewed professionals had already experienced situations with ethical conflicts and knew what ethical competence means. The central themes point out three fundamental issues in the construction of the ethical competence: personal values, education and practice. Taking into account that ethical competence is in permanent construction, the study shows the importance to promote organizational and educational activities in a transversal manner, as a tool to cope the moral stress and contribute in improving the quality of care in the primary health attention.